Studien zur Praxis der Übersetzung antiker Literatur - Kitzbichler, Josefine,Stephan, Ulrike C. A. (De Gruyter, 2016)
This volume is a collection of studies on the translation of Greek and Latin authors (Sappho, Alcaeus, Thucydides, Herodotus, Cicero, Ovid, Petronius, Apuleius), which examines the processes and conditions of translation as determined by reception history and genre, among others. The work is supplemented with an essay on the possibilities for developing a methodological basis for translation analysis and criticism.
10.1515/9783110422085
Keywords: Aufsatzsammlung; Griechisch; Latein; Literatur; Übersetzung; Deutsch